Micropropagação fotoautotrófica de amoreira-preta (Rubus spp.) e framboeseira (Rubus idaeus L.) com a utilização de luz natural. - Leitzke, Luciane Nolasco (2006)
The success of mass micropropagation of fruit trees may be reached by using plant tissues culture techniques, since this has showed efficient results on seedlings production with high quality and health. However, for the commercial viability of micropropagation application in the field of horticulture and how this might compete with traditional methods of propagation (cuttings, etc.), it is necessary to decrease production costs. Therefore, the development of photo-autotrophic micropropagation systems (production of micropropagules in sugar-free medium under environmental conditions that promote photosynthesis of the culture) with natural light appear as a possibility to improve the efficiency of micropropagation and to reduce costs. This research aimed the photo-autotrophic multiplication of blackberry (Rubus spp.) cultivar Xavante and raspberry (Rubus idaeus L.) cultivars Batum and Heritage. Preliminary experiments was carried out to define the constitution of culture medium that provides better results, as on multiplication as on in vitro rooting of blackberry and raspberry, under conventional conditions of micropropagation. Then, using the best constitution of culture medium, it was done the study of the photo-autotrophic multiplication by using natural light. The MS medium enriched with BAP at 13 µM was the more efficient treatment on in vitro multiplication of leaves of blackberry Xavante and raspberries Batum and Heritage , inducing a higher number of leaves, shoots and buds. The best rooting condition for explants of the blackberry Xavante was reached by keeping the explants in WPM enriched with 2,5 µM AIB for a week followed by a regulator-free medium growth. Nevertheless, for raspberry Batum rooting, it is necessary the addition of 6,5 µM AIB. Under photo- autotrophic conditions, the aluminum foil was the best sealing material for the flasks. Regarding to in vitro multiplication for blackberry cultivar Xavante the best growth local was in greenhouse with the addition of 22 g L -1 sucrose to the medium; and for raspberry Batum was at 11,5 g L-1 sucrose but kept in growth room. For in vitro rooting of raspberry Batum cotton was the best sealing material, growth room and sugar-free medium were the best condition having a higher rooting percentage and root numbers per explants.